PENGARUH PENATAUSAHAAN ASET TETAP TERHADAP KUALITAS LAPORAN KEUANGAN Studi Kasus pada BAPPEDA Kabupaten Lombok Barat - Yunarni, Baiq Reinelda Tri; Wirastomo, Handoyo (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to find empirical evidence in support of the hypothesis that there is an effect of fixed asset administration consisting of bookkeeping, inventory and reporting on the quality of financial reports (a case study at Bappeda West Lombok Regency). The method used in this research is quantitative method. With data analysis techniques using the help of the SPSS application program which includes validity, reliability, multiple linear regression analysis and coefficient of determination as well as hypothesis testing consisting of partial test or t test and simultaneous test or f test. The sample determination uses a non-probability sampling technique, namely the saturated sample method. Data collection is carried out through direct observation and surveys are carried out by distributing questionnaires to respondents. This study uses a multiple linear regression analysis model with SPSS 20 software. This study proves that there is a significant influence between the administration of fixed assets on the quality of financial reports at Bappeda West Lombok Regency.